Серумски рецептор за скавенгер растворљиве хемоглобина и Сестрин 2 код феталне хипоксије код трудница са гестационом хипертензијом: Серумски рецептор за апсорпцију растворљивог хемоглобина и Сестрин 2 код феталне хипоксије код трудница - Xie, Conghua; Liu, Qin; Wu, Wencheng; Wang, Liping; Tan, Hongyan (Journal of Medical Biochemistry, 2026)
[Objective] To assess the value of the serum levels of sestrin 2 (SESN2), heme oxidase 1 (HO-1), and soluble hemoglobin scavenger receptor (sCD163) for the prediction of intrauterine fetal hypoxia in pregnant women with gestational hypertension disorder (HDCP). [Methods] A total of 250 pregnant women with HDCP who were diagnosed and treated at this hospital from January 2023 to December 2024 were selected as the HDCP group, and 150 pregnant women with normal pregnancies who underwent prenatal examination at this hospital. Changes in the levels of serum SESN2, HO-1 and sCD163 in the two groups were observed, the levels of each index in pregnant women with HDCP of different severities were compared, and based on whether intrauterine fetal hypoxia occurred, the patients were split into two groups: those with intrauterine hypoxia and those without. The factors influencing intrauterine fetal hypoxia in pregnant women with HDCP and the predictive efficacy of serum SESN2, HO-1 and sCD163 levels for predicting intrauterine fetal hypoxia in pregnant women with HDCP were analyzed. [Results] The HDCP group had significantly higher levels of serum SESN2 and sCD163 than the normal pregnancy group (P<0.01), while the normal pregnancy group had significantly lower levels of serum HO-1 (P<0.01). Serum SESN2 and sCD163 levels were substantially greater in the severe preeclampsia group than in the moderate preeclampsia and gestational hypertension groups (P<0.01), while the mild preeclampsia and gestational hypertension groups had significantly lower serum HO-1 levels (P<0.01). Serum HO-1 levels in the mild preeclampsia group were significantly lower than those in the gestational hypertension group (P<0.01), while serum SESN2 and sCD163 levels were significantly higher than those in the latter group (P<0.01). While the intrauterine hypoxia group’s prothrombin time and HO-1 levels were significantly lower than those of the nonintrauterine hypoxia group (P<0.01), the intrauterine hypoxia group’s levels of serum D-dimer, fibrinogen (FIB), SESN2, and sCD163 were significantly higher. Multivariate logistic regression analysis revealed that elevated D-dimer, FIB, SESN2 and sCD163 levels were risk factors for intrauterine hypoxia in pregnant women with HDCP (P<0.05), whereas elevated prothrombin time and HO-1 levels were protective factors for intrauterine hypoxia in pregnant women with HDCP (P<0.05). The AUCs of individual and combined detection of serum SESN2, HO-1, and sCD163 for predicting intrauterine fetal hypoxia in pregnant women with HDCP were 0.825 (95%CI: 0.769–0.872), 0.869 (95% CI: 0.815–0.919), and 0.849 (95% CI: 0.797–0.892), 0.962 (95% CI: 0.928–0.983), and the AUC of the combined detection was significantly greater than that of SESN2 (Z=4.668, P<0.001), HO-1 (Z=4.878, P<0.001), and sCD163 (Z=4.226, P<0.001) single detection. [Conclusion] SESN2, HO-1 and sCD163 are involved in the occurrence and development of HDCP and are closely related to the severity of HDCP. The combined detection of these three indicators is helpful for determining the intrauterine hypoxia status of a fetus.